Antenatal Care Dengan Kejadian Pre Eklampsia Pada Ibu Hamil Di Puskesmas Pembina - Sutrisari Sabrina Nainggolan; Nur Wahyuni (HEALTH CARE: JURNAL KESEHATAN, 2023)
Pre-eclampsia is a fairly serious complication of pregnancy in which the blood pressure of pregnant women increases accompanied by protein in the urine. Pre-eclampsia is also one of the causes of morbidity and mortality in mothers and fetuses in the womb. To detect a pregnant woman having pre-eclampsia, it is important for pregnant women to do antenatal care. The purpose of this study was to determine the relationship between antenatal care and the incidence of pre-eclampsia at the Pembina Health Center. This research is an analytic survey research with a cross sectional approach. This research was conducted at the Pembina Health Center in May 2023. Respondents in this study were 89 pregnant women. Sampling technique with accidental sampling method. The analysis used was univariate analysis and bivariate analysis using the Chi-Square test. The results of this study showed that the majority of pregnant women did not receive antenatal care (50.6%), and 17 women (19.1%) experienced pre-eclampsia. The results of the Chi-Square statistical test showed that there was a relationship between antenatal care and the incidence of pre-eclampsia in pregnant women with a p value of 0.000. Therefore, the role of health workers is very important in providing counseling and motivation for pregnant women to carry out routine antenatal care, so that health workers can detect the symptoms of pre-eclampsia in pregnant women as early as possible.